Negishi-coupling-enabled synthesis of α-heteroaryl-α-amino acid building blocks for DNA-encoded chemical library applications - Gasparetto, Matteo; Fődi, Balázs; Sipos, Gellért (Beilstein Journal of Organic Chemistry, 2024)
Amino acids are vital motifs in the domain of biochemistry, serving as the foundational unit for peptides and proteins, while also holding a crucial function in many biological processes. Due to their bifunctional character, they have been also used for combinatorial chemistry purposes, such as the preparation of DNA-encoded chemical libraries. We developed a practical synthesis for α-heteroaryl-α-amino acids starting from an array of small heteroaromatic halides. The reaction sequence utilizes a photochemically enhanced Negishi cross-coupling as a key step, followed by oximation and reduction. The prepared amino esters were validated for on-DNA reactivity via a reverse amidation–hydrolysis–reverse amidation protocol.
Keywords: amino acids; DEL; flow chemistry; Negishi; on-DNA chemistry